"There Was Something Inside of Me I Needed to Let Out": Occupied Masculinities, Emotional Expression and Rap Music in a Palestinian Refugee Camp. (June 2022) - Skinner, Chloe
Although normative constructions of masculinity in Palestine denote emotional suppression as an idealized attribute, extreme subjugation under the grinding realities of a colonial military occupation requires that this ideal is negotiated. This article explores Palestinian rap as a channel through which emotions related to individual and collective oppression are expressed within the (fluid) parameters of a particular emergent masculine performance. Through qualitative research with young Palestinian men living in a refugee camp, I argue that emotional expression within this musical culture both functions to reconfigure binary gendered dynamics, while simultaneously masculinizing emotionality through a dialogic performance of emotion, nationalism, resistance, and paternalism. In some ways, patriarchal gendered binaries are hence challenged in and through the performance of Palestinian rap, while in other ways these are reconfigured so that men's emotional expression can be subsumed within them. This article, therefore, examines the negotiation of "masculinity as emotional suppression" through rap, in a context in which internal patriarchal powers are routinely threatened by colonial patriarchal forces.